(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Elisabeth LUB, Abinawanto, Sophian A, Julendra H, Sofyan A. 2020. The detection of plantaricin-encoding genes and amino acid profile in Lactobacillus plantarum AKK30 isolated from Indonesian native chicken. Biodiversitas 21: 5792-5799. Plantaricin-encoding genes of lactic acid bacteria (LAB) Lactobacillus plantarum AKK30 which was isolated from Indonesian native chicken has been characterized using DNA sequencing technology. In order to substitute antibiotics for chickens and enhance probiotics in their gut, characterization of the indigenous probiotics in the chicken should be conducted. A potential probiotic in native chicken gut is Lactobacillus plantarum AKK30. Genes that harbor the bacteriocin biosynthesis of the strain were reported for the first time. The bacterium has diverse plantaricin genes, i.e., plnA, plnEF, plnJ, plnK and plnO. According to the dendrogram, the five plantaricin genes were closely related to plnA, plnE, plnF, plnJ, plnK and plnO genes from L. plantarum WCFS1, L. plantarum C11, and L. plantarum V90. Intriguingly, besides various plantaricin-encoding genes, another important probiotic property in L. plantarum AKK30 is cholesterol-lowering activity. Amino acid profiling also indicated proteolysis activity and probiotic potential, for instance, GABA production. Thus, L. plantarum AKK30 may be added in chicken broiler’s diet to provide probiotic benefits.